Acute mechanical intestinal obstruction in children at zinder national hospital, Niger: Aetiologies and prognosis - Harissou Adamou; Ibrahim Amadou Magagi; Oumarou Habou; Ousseini Adakal; Kabirou Ganiou; Magagi Amadou (Wolters Kluwer Medknow Publications, 2017)
Background: To describe the aetiological and prognostic aspects of acute mechanical intestinal obstruction (AMIO) in children at Zinder National Hospital (Niger). Materials and Methods: This was a cross-sectional study on a period to January 2013-June 2015. The database included all children under 15 years of age with a surgical diagnosis of mechanical intestinal obstruction. P < 0.05 was considered statistically significant for analysis. Results: AMIOs represent 21.78% (n = 78) of child digestive surgical emergencies (n = 358). Median age was 12 months (range: 1 day-15 years). Fifteen (19.23%) were neonates and sixty children (76.92%) had ≤60 months. The sex ratio (male/female) was 2.8. The mean time from onset to presentation was 39.96 ± 36.22 h. Intussusception and strangulated hernias were the main causes of AMIO with, respectively, 43.59% (n = 34) and 29.48% (n = 23). Anorectal malformations represent 17.95% (n = 14) of cases of AMIO. Intestinal resection was made in 22.08% and colostomy in 19.23% of patients. The average length of hospital stay was 6.44 ± 4.30 days. The post-operative complications were recorded in 26 patients (33.33%), mostly surgical site infections. Overall mortality of AMIO was 15.38% (n = 12). It was higher in the neonates (33.33%) (P = 0.032). Deaths were associated with delay of admission (P = 0.0005) and waiting time for surgery (P = 0.019). Conclusion: Intussusception and strangulated hernia are the most common cause of AMIO in children. Diagnostic and therapeutic delays, lack of paediatric intensive care and post-operative complications are prognostic factors.